A novel bicistronic gene design couples stable cell line selection with a fucose switch in a designer CHO host to produce native and afucosylated glycoform antibodies. Issue 3 (3rd April 2018) - Roy, Gargi; Martin, Tom; Barnes, Arnita; Wang, Jihong; Jimenez, Rod Brian; Rice, Megan; Li, Lina; Feng, Hui; Zhang, Shu; Chaerkady, Raghothama; Wu, Herren; Marelli, Marcello; et al.
ABSTRACT: The conserved glycosylation site Asn 297 of a monoclonal antibody (mAb) can be decorated with a variety of sugars that can alter mAb pharmacokinetics and recruitment of effector proteins. Antibodies lacking the core fucose at Asn 297 (afucosylated mAbs) show enhanced antibody-dependent cell-mediated cytotoxicity (ADCC) and increased efficacy. Here, we describe the development of a robust platform for the manufacture of afucosylated therapeutic mAbs by engineering a Chinese hamster ovary (CHO) host cell line to co-express a mAb with GDP-6-deoxy-D-lyxo-4-hexulose reductase (RMD), a prokaryotic enzyme that deflects an intermediate in the de novo synthesis of fucose to a dead-end product, resulting in the production of afucosylated mAb (GlymaxX™ Technology, ProBioGen). Expression of the mAb and RMD genes was coordinated by co-transfection of separate mAb and RMD vectors or use of an internal ribosome entry site (IRES) element to link the translation of RMD with either the glutamine synthase selection marker or the mAb light chain. The GS-IRES-RMD vector format was more suitable for the rapid generation of high yielding cell lines, secreting afucosylated mAb with titers exceeding 6.0 g/L. These cell lines maintained production of afucosylated mAb over 60 generations, ensuring their suitability for use in large-scale manufacturing. The afucosylated mAbs purified from these RMD-engineered cell lines showed increased binding in a CD16 cellular assay, demonstrating enhancement of ADCC compared to fucosylated control mAb. Furthermore, the afucosylation in these mAbs could be controlled by simple addition of L-fucose in the culture medium, thereby allowing the use of a single cell line for production of the same mAb in fucosylated and afucosylated formats for multiple therapeutic indications.